Associations of ABO, D, and Lewis blood groups and HLA Class I and Class II alleles with West Nile virus Lineage 2 disease outcome in Greece, 2010 to 2013. Issue 8 (1st June 2016) - Politis, Constantina; Parara, Myrsini; Kremastinou, Jenny; Hasapopoulou, Eleni; Iniotaki, Aliki; Siorenta, Alexandra; Richardson, Clive; Papa, Anna; Kavallierou, Lilian; Asariotou, Marina; Katsarou, Olga; Mougiou, Athina; et al.
Abstract : BACKGROUND: West Nile virus (WNV) infection, commonly asymptomatic, may cause mild West Nile fever (WNF) or potentially fatal neuroinvasive disease (WNND). An outbreak of 262 cases of the new Lineage 2 strain in Greece in 2010 continued with high mortality (17%) in WNND. The objective was to investigate ABO, D, and Lewis blood groups, as well as HLA Class I and Class II alleles, in relation to WNV Lineage 2 disease morbidity. STUDY DESIGN AND METHODS: A cohort of 132 Greek WNV cases in 2010 to 2013 (65% male; mean age 64 years; 41% WNF, 59% WNND) was compared to 51, 339 healthy WNV‐negative blood donors and 246 healthy subjects. RESULTS: Blood group A was more common in WNV cases (51%) than blood donors (39%) and group O less common (32% vs. 42%). D negativity within group A was higher in WNV than in blood donors (18% vs. 10%, p = 0.044). The frequency of secretors (Lewis(a–b+)) was 60% in WNV and 68% in donors (p = 0.16). HLA alleles C*08, DRB1*O4:O5, and DQB1*O2 occurred significantly less frequently in WNV than controls (p < 0.05 unadjusted for multiple testing) and DRB1*10:O1 more frequently (p = 0.039). CONCLUSION: This first study of symptomatic WNV Lineage 2 suggests A/D negativity as a new risk factor associated with WNV infection and level of morbidity. Further studies are required of the possibility that HLA C*08, DRB1*O4:O5, and DQB1*O2 are protective alleles and DRB1*10:O1 a "susceptible" allele to WNV infection and the role of secretor status in relation to WNV infection.